Metafora Hewan Dalam Ungkapan Peribahasa Dorabololo Masyarakat Ternate - Nurbaya Nurbaya; Sukardi Abbas (KOLONI, 2026)
Metaphor interprets human perspective through an object. One of them is animal object in giving meaning to every aspect of human life. This article describes how certain animals are used in Ternate dorabololo proverbs to describe various experiences, behaviors, and the causes behind people's behavior. This study uses Conceptual Metaphor Theory. This theory describes the mapping of two domains known as the source domain and the target domain which has been widely adopted in the analysis of metaphorical expressions related to various concepts. Data collection was carried out by purposive sampling from both primary and secondary sources. Data analysis was carried out by categorizing and discussing the data under relevant thematic subheadings. The findings in this study revealed that both invertebrate and non-invertebrate animals such as birds, fish, and insects are expressed in Ternate dorabololo proverbs to advise people against undesirable negative attitudes or behaviors such as being untrustworthy, irresponsible, procrastination, greed, and all kinds of other social evils. These creatures are also used through the proverb dorabololo as a guide to life that directs towards positive behavior that can be used as a learning resource in learning Indonesian language and literature.